2007
DOI: 10.1002/cne.21534
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of Kir2.1 subunits in neurons and glia in piriform cortex with implications for K+ spatial buffering

Abstract: Potassium channels of the Kir2 family are widely expressed in neurons and glia, where they form strong inwardly rectifying channels. Existing functional hypotheses for these channels in neurons are based on the weak outward conductance, whereas the leading hypothesis for glia, that they promote potassium spatial buffering, is based on inward conductance. Although the spatial buffering hypothesis has been confirmed for Müller glia in retina, many aspects of Kir2 channels that will be required for understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 97 publications
5
23
1
Order By: Relevance
“…Pyramidal neurons in the neocortex and hippocampus have a large I h , particularly in dendrites where I h is thought to normalize or scale synaptic inputs (Williams and Stuart 2000). Although it has been reported that piriform pyramidal neurons do not express I h (e.g., Howe et al 2008), we observed small, but consistent sags in AON, piriform, and pEN neurons, most likely resulting from I h . A small I h , as well as the results of our passive cable analysis, is consistent with a more passive and compact dendritic tree in piriform pyramidal neurons compared with neocortex (Bathellier et al 2009;Spruston 2008).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Pyramidal neurons in the neocortex and hippocampus have a large I h , particularly in dendrites where I h is thought to normalize or scale synaptic inputs (Williams and Stuart 2000). Although it has been reported that piriform pyramidal neurons do not express I h (e.g., Howe et al 2008), we observed small, but consistent sags in AON, piriform, and pEN neurons, most likely resulting from I h . A small I h , as well as the results of our passive cable analysis, is consistent with a more passive and compact dendritic tree in piriform pyramidal neurons compared with neocortex (Bathellier et al 2009;Spruston 2008).…”
Section: Discussioncontrasting
confidence: 49%
“…pEN principal neurons had a pronounced inward rectification, consistent with a higher expression of IRK and/or GIRK channels. In olfactory cortex, neurons, rather than glia, may buffer extracellular potassium, during local increases in extracellular potassium such as seizures (Howe et al 2008). Therefore, a high potassium buffering capacity of pEN neurons could be important in controlling excitation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, absence seizures also negligibly affected the expression of Kir2.1, which even at low levels is also expressed in the astrocytes of several brain regions (e.g. piriform cortex and olfactory bulb) (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The expressional level of the Kir2.1 subunit was evaluated since Kir2.1 channels are also known to be expressed in astrocytes even at low density (26,27).…”
Section: Objectivesmentioning
confidence: 99%
“…K ir 2.1 homotetramers form an inwardly-rectifying K 1 channel (Yang et al, 1995;Collins et al, 1997;Hibino et al, 2010) that is widely expressed throughout the central nervous system (Bredt et al, 1995;Horio et al, 1996;Howe et al, 2008), as well as in cardiac, smooth, and striated myocytes (de Boer et al, 2010;Hibino et al, 2010). Genetic knockout of K ir 2.1 in mice results in death 8-12 hours after birth (Zaritsky et al, 2000); conversely, overexpression of K ir 2.1 leads to a 10-mV hyperpolarization in neuronal resting membrane potential and suppressed neuronal firing (Burrone et al, 2002;Béïque et al, 2011).…”
Section: Disrupted Subcellular Dynamics Of S-1r Mutantsmentioning
confidence: 99%